Percutaneous epidural balloon decompression and neuroplasty by ZiNeu catheter in lumber spinal stenosis patient in Bangladesh: A case report - Das, Rajat Shuvra; Saha, Sanjoy Kumar; Saha, Panna Lal; Shin, Jin-Woo; AKM Akhtaruzzaman (Bangabandhu Sheikh Mujib Medical University Journal, 2025)
Not available